INCREASING STUDENTS AWARENESS OF SCHOOL DISCIPLINE THROUGH THE GESTALT APPROACH IN GROUP COUNSELING - Rahayu Dewany; Netrawati (Yayasan Citra Dharma Cindekia, 2021)
Discipline is a condition in which a person obeys and implements the provisions, rules, regulations, values and rules that apply with self-awareness without coercion, but in reality many students are less aware of discipline in schools so that they violate existing rules and norms. in schools, such as research conducted by Peti Pitriani whose research results state that students' low awareness of school discipline is influenced by students' external factors. even though one way to achieve learning goals is to obey all applicable disciplines. Conselor have a very important role in increasing students' awareness of school discipline, namely by carrying out counseling service activities with a gestalt approach to students who violate school discipline, because the purpose of the gestalt counseling approach is to increase awareness for students because by increasing students' awareness of school discipline the learning objectives will be achieved optimally.